Weighted Composition Operators from the Zygmund Space to nth Weighted-Type Spaces. (9th September 2020) - Abbasi, Ebrahim; Li, Songxiao
Abstract: In this work, the boundedness and essential norm of weighted composition operators from the Zygmund space to n th weighted-type spaces are characterized. As a corollary, some characterizations for the compactness of weighted composition operators from the Zygmund space to n th weighted-type spaces are also presented.